Expression of foxp3 tumour infiltrating lymphocytes in her2 positive breast cancer and their association with clinicopathological features - Hashim, Sobry (2023)
Background: The transcription factor Forkhead Box Protein P3 (FOXP3) plays a crucial role in regulatory T cells (Tregs) development and function and serves as a lineage specification factor of Tregs. FOXP3+ tumour infiltrating lymphocytes (TILs) are considered significant prognostic markers in breast cancer. However, the prognostic significance of FOXP3+ TILs in human epidermal growth factor receptor 2 (HER2) positive breast cancers remains controversial. We investigated the proportion of HER2-positive breast cancer and their expression of FOXP3+ TILs and evaluated their association with clinicopathological features. Methods: A cross-sectional study was conducted involving 167 formalin-fixed paraffin-embedded (FFPE) tissue samples of HER2-positive breast cancer cases from the Department of Pathology, Hospital Sultanah Nur Zahirah (HSNZ) from the year of 2014 to 2021. The tissue sections were stained with immunohistochemistry (IHC) anti-FoxP3 antibodies. FOXP3+ TILs expression was categorised into low infiltration (grade 0 to grade 1) and high infiltration (grade 2 to grade 3). Fischer’s Exact test was used to analyse the association with clinicopathological characteristics. A p-value of less than 0.05 was considered statistically significant. Results: Total breast cancer cases from 2014-2021 were 1066 cases. There were 272 (25.5%) HER2-positive breast cancer cases. Among 167 selected HER2-positive breast cancer cases, 164 (98.2%) cases showed strong FOXP3+ TILs infiltration, and 3 (1.8%) cases showed low infiltration. There was no significant association between the expression of FOXP3+ TILs with the age of diagnosed (p > 0.950), tumour grade (p=0.091), tumour size (p=0.235), axillary nodal status (p=0.552), metastasis status (p > 0.950), oestrogen receptor (ER) status (p=0.616) and progesterone receptor (PR) status (p > 0.950). Conclusion: FOXP3+ TILs were highly infiltrating HER2-positive breast cancer despite variability in clinicopathological characteristics.